2023
DOI: 10.1002/arch.22057
|View full text |Cite
|
Sign up to set email alerts
|

Insect cuticle and insecticide development

Yunuo Ren,
Ying Li,
Yingjie Ju
et al.

Abstract: Insecticide resistance poses a significant challenge, diminishing the effectiveness of chemical insecticides. To address this global concern, the development of novel and efficient pest management technologies based on chemical insecticides is an ongoing necessity. The insect cuticle, a highly complex and continuously renewing organ, plays a crucial role in this context. On one hand, as the most vital structure, it serves as a suitable target for insecticides. On the other hand, it acts as the outermost barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 78 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…odoriphaga. As an exoskeleton, the epidermis is involved in maintaining body stability and resistance to various harmful environments . The results suggested that BoAhR and BoARNT might be particularly important in the environmental stress signal transduction and defense response.…”
Section: Discussionmentioning
confidence: 98%
“…odoriphaga. As an exoskeleton, the epidermis is involved in maintaining body stability and resistance to various harmful environments . The results suggested that BoAhR and BoARNT might be particularly important in the environmental stress signal transduction and defense response.…”
Section: Discussionmentioning
confidence: 98%
“…Addressing insecticide resistance through novel pest management technologies requires understanding the complex role of the insect cuticle as both a target and a barrier for chemical insecticides. This understanding offers insights for developing effective solutions in pest management [121].…”
Section: • Dysregulation Of Insect Development In Different Stages Of...mentioning
confidence: 98%